2013
DOI: 10.2527/jas.2012-5281
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid digestibility and concentration of digestible and metabolizable energy in copra meal, palm kernel expellers, and palm kernel meal fed to growing pigs

Abstract: Two experiments were conducted to determine apparent ileal digestibility (AID) and standardized (SID) ileal digestibility of AA (Exp. 1) and the concentration of DE and ME (Exp. 2) in copra meal (CM), palm kernel expellers from Indonesia (PKE-IN), palm kernel expellers from Costa Rica (PKE-CR), palm kernel meal from Costa Rica (PKM), and soybean meal (SBM). In Exp. 1, 6 barrows (BW = 34.0 ± 1.4 kg) were randomly allotted to a 6 × 6 Latin square design with 6 diets and 6 periods. One diet contained 30% SBM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
48
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 41 publications
14
48
3
Order By: Relevance
“…The concentrations and digestibility of energy in the corn germ meal were within the range of previous values [2,4,21,23, 29]. The GE, DE, and ME in the palm kernel expellers were also within the range of previous studies [2,4,5,27]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The concentrations and digestibility of energy in the corn germ meal were within the range of previous values [2,4,21,23, 29]. The GE, DE, and ME in the palm kernel expellers were also within the range of previous studies [2,4,5,27]. …”
Section: Discussionsupporting
confidence: 82%
“…It has been known that the dietary glucosinolates have an adverse effect on the feed intake for pigs [26]. The GE, DE, and ME in the copra meal used in this experiment were less than those reported in the literature [4,27]. In particular, the DE:GE ratio of copra meal was less in our study compared with the previous values.…”
Section: Discussioncontrasting
confidence: 69%
“…The EE contents observed in palm kernel meal and copra meal were high, indicating inefficient oil extraction from the original materials. A study of Sulabo et al (2013) reported that the EE contents of palm kernel meal and copra meal were 1.3% and 1.9% DM, respectively; these results were more than one-fourth lower compared to the results obtained in the present experiment. Such high EE may shorten the shelf-life of palm kernel meal and copra meal due to oxidation and rancidity processes during the storage.…”
Section: Chemical Composition Of Feedstuffscontrasting
confidence: 56%
“…Peanut meal (PNM) is a by-product of oil extraction from whole or broken peanuts and the solvent-extracted PNM is increasingly being used as an animal feed (Dale and Batal 2005), since the tight supply of protein sources drives feed manufacturers to pay more attention to more economical protein ingredients in place of soya bean meal (Sulabo et al 2013). Annual global production of peanuts has been on the increase, reaching 35 million tons in recent years, while 12 million tons were generated in China alone, accounting for 34% of world production (Revoredo and Fletcher 2002).…”
Section: Introductionmentioning
confidence: 99%